ROLE LEADERSHIP IN TRANSFORMATION MANAGEMENT AND ORGANIZATION BASED ON TECHNOLOGY ADVANCED (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
The transformation of management and organizations based on advanced technology presents both challenges and opportunities for leaders in the digital era. This article discusses how leadership plays a strategic role in directing organizational change through the implementation of innovative technology. Using a descriptive qualitative method, this research explores the aspects of leadership that contribute to the success of organizational transformation. The study results show that adaptive, visionary, and data-driven leadership can enhance the effectiveness, flexibility, and efficiency of the organization. This study also identifies the main challenges and strategies that can be applied to overcome obstacles in the implementation of advanced technology in organizational management. This study also identifies the main challenges and strategies that can be applied to overcome obstacles in the implementation of advanced technology in organizational management